Diversity of free-living amoebas in the Monjolinho River in São Paulo state – morphological and molecular approaches - Bellini, Natalia Karla (2020)
Free Living Amoeba (FLA) has gained increasing visibility due to human health concerns. They are unicellular heterotrophic protozoans, widely spread in nature. Water is the main source of amoebic contaminations that may result in encephalitis, keratitis, and skin infections. Pathogenic species belong to the Naegleria, Acanthamoeba, Sappinia, Balamuthia, and Hartmannella genera. To date, there is a lack of effective treatment and accurate diagnosis for amoebic infections, which has motivated the environmental characterization of FLA as a human health risk assessment strategy. However, FLA epidemiology in Brazil is scarce, contrasting with the country´s freshwater abundance. To address this gap, the present research aimed at the FLA characterization along the Monjolinho River, São Carlos, Brazil. The water abiotic evaluation as well as the morphological, and molecular investigation of FLA encompasses the central methodology. Dissolved oxygen and electrical conductivity were measured as the most informative features to inspect anthropogenic driving forces acting upon the hydric ecosystem. Eutrophic sites, downstream of the urban areas, were revealed as hotspots to a diversity of FLA. Non-nutrient agar (NNA) plates seeding confirmed the amoeba growth by light and electron microscopy characterization. Based on these results, relevant taxonomic details (e.g.: flagella, cyst walls, and pseudopodia branching patterns) were described to all FLA life cycle stages. Axenization attempts revealed the persistence of bacteria contamination, suggestive of the presence of amoebic resistant microorganisms, enhancing its threat to humans. Molecular characterization enabled us to detect the potentially pathogenic genera Naegleria (N. australiensis and N. phillipinensis), Acanthamoeba (A. genotype T4 and A. hatchetti), and Hartmanella (V. vermiforms); besides the non-pathogenic Vannela sp, Stenamoeba, Filamoeba, and Naegleria (N. canariensisi, N.gruberi, and N. dobsoni). In this work, the knowledge of FLA distribution allowed the recognition of Brazilian freshwaters as suitable ecological niches to FLA spread, as well as the development of the methodology necessary for the future identification and characterization of FLA in the environment. Although conducted to a local extend, this research suggests that other FLA genus can be equally isolated in Brazilian freshwater systems that can finally booster later expansion to other water streams.